Victorian Alpine Plot Network (ATEX): Vegetation Change and Phenology in Response to Increased Temperature, South-east Highlands, Australia, 2004–2014 - Ary Hoffmann; Henrik Wahren; James Camac; The University of Melbourne; Research Centre for Applied Alpine Ecology, La Trobe University (TERN Australia, 2015)
This data package shows the effects of experimental warming on plants in the Victorian Alpine region between 2004–2014. These data are from the Australian Tundra Experiment (ATEX) which is part of the International Tundra Experiment (ITEX). The data tables consist of a subset of previously published data packages which have been combined to demonstrate the conclusions discussed on pages 188–191 of the book Lindenmayer et al., 2014. Biodiversity and Environemntal Change: Monitoring, Challenges and Direction (Core Study 4. Climate change experiment in open heathlands/grassland, Bogong High Plains). They also include data which has been collected since the book had been published. This experiment looks at the effects of increasing the near-surface soil temperature by ~1–2°C. As a consequence, the cover of grasses decreased in cover, while both forbs and shrubs increased in cover. Diversity increased as a result of changes in relative abundance and most growth forms increased in height. The ATEX experiment is locate at four sites on the Bogong High Plains, each site comprising multiple 1 square metre plots. The composition of each plot is sample using point quadrats every second snow-free season. The Victorian Alpine Plot Network research plots are revisited on a biannual basis, though measurements taken during surveys differ from visit to visit. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine